Fermented whey as poultry feed additive to prevent fungal contamination - Londero, Alejandra (2014)
BACKGROUND: Fungal contamination of poultry feed causes economic losses to industry and represents a potential risk to animal health. The aim of the present study was to analyze the effectiveness of whey fermented with kefir grains as additive to reduce fungal incidence, thus improving feed safety. RESULTS: Whey fermented for 24 h at 20 ∘C with kefir grains (100 g L−1) reduced conidial germination of Aspergillus flavus, Aspergillus parasiticus, Aspergillus terreus, Aspergillus fumigatus, Penicillium crustosum, Trichoderma longibrachiatum and Rhizopus sp. Poultry feed supplemented with fermented whey (1 L kg−1) was two to four times more resistant to fungal contamination than control feed depending on the fungal species. Additionally, it contained kefir microorganisms at levels of 1 × 108 colony-forming units (CFU) kg−1 of lactic acid bacteria and 6 × 107 CFU kg−1 of yeasts even after 30 days of storage. CONCLUSION: Fermented whey added to poultry feed acted as a biopreservative, improving its resistance to fungal contamination and increasing its shelf life